Perfluoro-1, 3-dioxolane and perfluoro-oxetane: promising gases for electrical insulation. (26th November 2018) - Hösl, Andreas; Pachin, Juriy; Chachereau, Alise; Kornath, Andreas; Franck, Christian M
Abstract: Perfluorinated cyclic ethers represent an interesting class of molecules to use as dielectric gases for electrical insulation. Measurements of the two compounds 4, 4, 5, 5-tetrachloro-2, 2-difluoro-1, 3-dioxolane (, CAS 87075-01-2) and octafluoro-1, 4-dioxane (, CAS 32981-22-9) in a pulsed Townsend experiment are presented, their ionization and attachment rate coefficients are obtained and their electron attachment cross sections are estimated. Both gases have a high critical electric field strength of about and times the one of SF, respectively, which is presumably due to very high electron attachment cross sections in the range from 2–4 eV. In particular, for the values appear to be very close to the S-wave scattering limit around 3 eV. Based on these results, we recommend the two analogous compounds perfluoro-1, 3-dioxolane (, CAS 21297-65-4) and perfluoro-oxetane (, CAS 425-82-1) for further research for the use as insulation and refrigerant gases, since they are chemically comparable, presumably environmentally friendly, and have high vapor pressures.